Effect of different concentration of sodium hydroxide [NaOH] of sodium hydroxide [NaOH] on Kenaf sandwich structures - Abdul Aziz, Mohammad; Halim, Zahurin; Othman, Maizatulnisa (Institute of Physics Publishing, 2018)
Sandwich panels are structures that made of three layers, low-density core inserted in between thin skin layers. This structures allow the achievement of excellent mechanical performance with low weight, thus this characteristic fulfil requirement to be use in aircraft application. In recent time, sandwich structures have been studied due to it has multifunction properties and lightweight. The aim of this study is to fabricate a composite sandwich structures with biodegradable material for face sheet [skin] where the fibre being treat with different concentration of sodium hydroxide [NaOH] with 10 and 20 hours of soaking time. Kenaf fibre [treated] reinforced epoxy will be used as skins and Nomex honeycomb is chosen to perform as core for this sandwich composite structure. The mechanical properties that are evaluated such as flexural strength and impact energy of kenaf fibre-reinforced epoxy sandwich structures. For flexural test, the optimum flexural strength is 13.4 MPa and impact strength is 18.3 J.